2005
DOI: 10.1001/jama.293.3.311
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Quality Improvement Intervention for Adolescent Depression in Primary Care Clinics

Abstract: 15% to 20%, 1 current prevalence is estimated as high as 6%, 2 and 28.3% of adolescents report periods during the past year of depressive symptoms leading to impairment. 3 Untreated depression is associated with suicide, a leading cause of death for youth aged 15 to 24 years, 4,5 and with other negative outcomes including school dropout, pregnancy, substance abuse, and adult depression. 2,[5][6][7][8][9] The treatment literature supports efficacy for cognitive-behavior therapy (CBT), 10-14 interpersonal psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
377
3
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 436 publications
(400 citation statements)
references
References 61 publications
16
377
3
3
Order By: Relevance
“…It has a well-established record of use as a screener for depressive symptomatology in adolescent samples (e.g., Asarnow, Jaycox, Duan, LaBorde, Rea, Murray, et al, 2005;Dierker, Albano, Clarke, Heimberg, Kendall, Merikangas, et al, 2001;Roberts, Lewinsohn, & Seeley, 1991). As described above the CES-D was used as the initial gate of a two-stage recruitment and screening procedure.…”
Section: Methodsmentioning
confidence: 99%
“…It has a well-established record of use as a screener for depressive symptomatology in adolescent samples (e.g., Asarnow, Jaycox, Duan, LaBorde, Rea, Murray, et al, 2005;Dierker, Albano, Clarke, Heimberg, Kendall, Merikangas, et al, 2001;Roberts, Lewinsohn, & Seeley, 1991). As described above the CES-D was used as the initial gate of a two-stage recruitment and screening procedure.…”
Section: Methodsmentioning
confidence: 99%
“…107 There are no systematic reviews or metaanalyses evaluating provider communication per se, but care coordination interventions requiring interprovider communication have led to positive outcomes in pediatric and child mental health settings. 8,108,109 Adult collaborative care intervention studies, including meta-analyses, provide similar evidence. 110,111 Practice Implications…”
Section: Rationale and Evidencementioning
confidence: 83%
“…6 Adolescent depression is associated with negative academic, social, and health outcomes, including depression in adulthood, substance abuse, early pregnancy and parenthood, higher medical expenses, and increased suicide risk. 2,[7][8][9][10][11][12][13][14][15] Despite the high burden of depression and the availability of effective treatments, up to 80% of affected adolescents do not receive appropriate care. 2,[16][17][18][19] The challenging task of identifying adolescents with depression falls disproportionately to pediatricians, as most depressed adolescents present in primary rather than specialty care.…”
mentioning
confidence: 99%
“…[6][7][8] One of these studies 6 , in which young people were invited to attend a nurse-led general-practice visit reported only minor changes in participants' health-risk behaviours. The other studies, which focused on reductions in sexual-risk behaviours, reported a positive effect of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The other studies, which focused on reductions in sexual-risk behaviours, reported a positive effect of the intervention. 7,8 In a study, information and education activities of health workers in health facilities were considered key contributors to the changes in reported behaviors of the adolescents. 9 Most studies suggest that access to all settings can be improved through youth-friendly interventions.…”
Section: Discussionmentioning
confidence: 99%